TINJAUAN KELENGKAPAN FORMULIR RINGKASAN MASUK DAN KELUAR PASIEN RAWAT INAP BERDASARKAN ANALISIS KUANTITATIF PENYAKIT CATARACK, UNSPECIFIED DI RUMAH SAKIT ISLAM AMAL SEHAT SRAGEN - Liss Dyah Dewi Arini; Marisca Windi Absari; Sri Wahyuningsih Nugraheni (Jurnal Keperawatan Duta Medika, 2022)
Introduction: Efforts to improve hospital quality need to be carried out to assess hospital services, namely by conducting quantitative analysis. Objectives: To find out the completeness of filling in and out summary forms for inpatients based on quantitative analysis of catarack disease, unspecified at the Amal Sehat Islamic Hospital, Sragen. Methods: This research is a descriptive study, using the method of observation and interviews. The population in this study were 616 medical records of inpatients with cataracts, unspecified by using a random sampling technique where the sample was taken randomly and the Slovin formula was used to determine the sampling. Result: analysis in the review of identification of the complete number of 240 documents with a percentage of 98.77% while those that were incomplete were 3 documents with a percentage of 1.23%, in the review of reporting the complete number of 123 documents with a percentage of 50 ,62% while the incomplete ones are 120 with a percentage of 49.38%, in the authentication review the complete number is 236 documents with a percentage of 97.12% while the incomplete ones are 7 documents with a percentage of 2.88% and in the recording review the total number is 2.88%. 236 complete documents with a percentage of 97.12% while 7 documents incomplete with a percentage of 2.88% Conclusion: the incompleteness of medical record documents at the Amal Sehat Hospital Sragen is still not optimal, medical and non-medical officers should be more careful in completing medical record documents.